Urinary Neutrophil Gelatinase-Associated Lipocalin (NGAL) and Cystatin C in Early Detection of Pediatric Acute Kidney Injury; a Diagnostic Accuracy Study - Neamatollah Ataei (Archives of Academic Emergency Medicine, 2018)
Introduction: There is a controversy regarding accuracy of neutrophil gelatinase-associated lipocalin (NGAL) and Cystatin C in early detection of acute kidney injury (AKI). The present study aimed to compare the diagnostic value of two biomarkers in this regard.